What is the diagnostic utility of endoscopic scoring systems in children? - ÇELİKEL, ÇİĞDEM; ERTEM ŞAHİNOĞLU, DENİZ; TUTAR, ENGİN (AVES, 2013)
Background/aims: The aim of this study was to evaluate the consistency of the Savary-Miller, the Hetzel-Dent and the Los Angeles endoscopic classification systems and to compare them with the esophageal histopathology in children. Material and Methods: Children between the ages of 5-17 years who underwent esophagogastroduodenoscopy were included in the study. The endoscopic reports and the still images of the esophagus were reclassified by the same gastroenterologist according to the Savary-Miller, Hetzel-Dent and Los Angeles scoring systems. The esophageal biopsies were also reevaluated by the same pathologist and the consistency between endoscopic and histopathologic esophagitis was evaluated. Results: A total of 113 out of 192 pediatric patients were included in the study. Seventy-three patients (64.6%) had esophagitis according to the Hetzel-Dent classification, whereas only 20 (17.7%) patients were defined as having esophagitis according to the other two classification systems. The consistency between the Savary-Miller and Los Angeles classifications was excellent (kappa: 0.92) but the agreement between the Hetzel-Dent and Savary-Miller and between the Hetzel-Dent and Los Angeles classifications were poor. A total of 82 patients (72.6%) had histopathological esophagitis, and there was a weak consistency between all 3 endoscopic scoring systems and the histopathology. Conclusions: Since pediatric patients have milder esophagitis than in adults, the use of endoscopic scoring systems developed for adults seems to be inapplicable for children. The inclusion of minimal endoscopic changes in endoscopic scoring systems by using more sensitive and novel endoscopic techniques would increase the sensitivity of these scoring systems in children.
Keywords: Gastroesophageal reflux; endoscopic esophagitis; endoscopic classification system; children; GASTROESOPHAGEAL-REFLUX DISEASE; LOS-ANGELES CLASSIFICATION; DILATED INTERCELLULAR SPACES; EVIDENCE-BASED CONSENSUS; EROSIVE ESOPHAGITIS; PEDIATRIC-GASTROENTEROLOGY; INTEROBSERVER AGREEMENT; EUROPEAN-SOCIETY; NATURAL-HISTORY; SYMPTOMS